Sistem Penyimpanan Kemuseuman - Yuni Larasanti Nurhasanah br Sitepu; Muhammad Perdana Algusti Tarigan; Chindi Ros Mava Siregar (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The storage system is essential forining, preserving,ining and managing the museum's collection. The aim of this research is to develop and evaluate effective, secure, and accessible storage systems for a wide range of museum collections. The research also focuses on analyzing the storage systems of humanity and covers theories and concepts related to the management and organization of valuable collections in museums. In this research we use methods of study of descriptive literature. We collect and analyze data from a variety of literary sources, including books, journals, and study reports related to this research topic. This research shows that the storage system of humanity consists of several important parts, such as planning, organization, management, and supervision. We also found many principles and approaches used in museums to ensure that valuable collections are of high quality and secure. This research forms the basis for the development of a more efficient, efficient and high-quality human storage system, as it answers a number of unanswered questions about the system's development. The result is that this study provides a general overview of the storage system of art and shows that many aspects that need to be optimized in the management of collections are valuable in the museum. And it shows that the use of a digital storage system not only improves operational efficiency but also reduces the risk of damage to the collection. It also allows museum managers to access the collection data faster and more accurately. In addition, it is proven that the use of proper storage materials protects the physical condition of the collection from environmental damage such as extreme humidity and temperatures.